2014
DOI: 10.1161/hypertensionaha.113.02535
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Treatment Attenuates Increased Respiratory Variability and Apnea/Hypopnea Index in Rats With Chronic Heart Failure

Abstract: Cheyne-Stokes respiration (CSR) and cardiac arrhythmias are associated with increased morbidity and mortality in patients with congestive heart failure (CHF). Enhanced carotid body chemoreflex (CBC) sensitivity is associated with these abnormalities in CHF. Reduced carotid body nitric oxide and nitric oxide synthase (NOS) levels play an important role in the enhanced CBC. In other disease models, Simvastatin (statin) treatment increases endothelial NOS (eNOS) in part by increasing Kruppel like Factor 2 (KLF2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 58 publications
(71 reference statements)
1
48
0
Order By: Relevance
“…Blood pressure was measured in conscious, freely moving rats using radiotelemetry as previously described (Haack et al, 2014). In brief, animals were anesthetized with 2–4% isoflurane via inhalation.…”
Section: Methodsmentioning
confidence: 99%
“…Blood pressure was measured in conscious, freely moving rats using radiotelemetry as previously described (Haack et al, 2014). In brief, animals were anesthetized with 2–4% isoflurane via inhalation.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, simvastatin has been shown to reduce the incidence of arrhythmias and oscillatory breathing and reduce CB chemoreflex sensitivity in CHF rats (Haack et al , 2014). These improvements corresponded with an increase in KLF2 and eNOS expression and a decrease in AT1R expression in the CB.…”
Section: Translational Impact Of Cb Hyperactivity In Chfmentioning
confidence: 99%
“…Indeed, therapeutic doses of statins decrease Rho kinase activity in patients with atherosclerosis in an LDL-independent manner 63 . Our lab has similarly found that statin treatment improves autonomic function in experimental and clinical heart failure independent of LDL-lowering effects 6468 , and clinical studies in patients with hypertension and chronic kidney disease support the sympatholytic effect of statins in humans regardless of the presence of hyperlipidemia 6972 . Given the strong associative 7375 and experimental 76,77 data linking autonomic function and mortality in cardiovascular disease, the sympatholytic effects of statins through Rho kinase inhibition may be an important mechanism by which these drugs reduce cardiovascular risk.…”
Section: Discussionmentioning
confidence: 75%